SUCCESS RATE OF MICRO-PERCUTANEOUS NEPHROLITHOTOMY IN THE TREATMENT OF RENAL CALCULI - Muhammad Muzammil Tahir (Journal of University Medical & Dental College, 2018)
ABSTRACT: BACKGROUND: The gold standard treatment option for moderate to huge sized kidney stones has been percutaneous nephrolithotomy for many years. Micro-percutaneous nephrolithotomy (microperc) has been done progressively for medium-sized renal calculi. It is really important to completely clear the renal stones because of high recurrence rate and morbidity in both conventional PNL, and microperc techniques. PURPOSE: To determine the frequency of success in terms of stone free state 4 weeks after microPNL among patients with renal stones STUDY SETTING: Urology Department, Shaikh Zayed Hospital, Lahore. PERIOD OF STUDY: August 17, 2016 to February 17, 2017. SUBJECTS & METHODS: A total of 60 patients with kidney stone of <2 cm in size and between 18 to 60 years of age were enrolled. Micro-PNL was done after accomplishment of all investigations. All stpatients were given prophylactic antibiotics. Stone free rate at 1 post-operative day and 1 month post-operatively was assessed by Xray or Ultrasound KUB. The stone free rate after one month was the endpoint of this study. The data were entered and analyzed by using SPSS 23.0. Data were stratiﬁed for age, gender and stone size to address the eﬀect modiﬁers. Post stratiﬁcation, Chi-square test was applied to check the signiﬁcance with p-value ≤ 0.05 as signiﬁcant. RESULTS: Sixty patients with renal calculi were enrolled. Among these patients, 39(65%) were males, while 21(35%) were females. Age range in this study was from 18 to 60 years with mean age of 39.35±13.56 years. Mean size of the stone was 0.93±0.13. Most of the patients 42(70%) had the size of stone <1 cm, while 18(30%) patients had the size of stone >1 cm. Overall success rate of micro-PNL was 86.7% in patients with renal calculi. CONCLUSION: The micre-PNL technique is eﬃcaceous and safe for stones with low morbidity, signiﬁcant success rate and acceptable operative time span.